Contact between children absent in state care and their families: The parents' perspective. (December 2022) - Clapton, Gary; Simpson, Jennifer; Grant, Catriona
This paper reports on survey work and group discussion by a Scottish parent-led support group (Parents Advocacy and Rights – PAR) that supports parents with children in the care system. A previous paper has been published discussing an overview of the survey results (www.pfan.uk/uncovering-the-pain/ ). The present paper delves further into parents' particular experiences of contact. The responses are preceded by a critical retrospective of the concept of contact. Our retrospective covers the language of contact, contact's origins, continuing confusions of meaning and the lack of appreciation of the parental experience and points to the artificiality of contact, the impracticalities of contact arrangements and the toll taken by these. We conclude by pointing out that we are in the fourth decade of recommendations about contact between parents and children in state care. We make the observations that there is a continuing failure to empathise with parents' experience of deprivation and loss, a lack of comprehension of the depth of detriment to parental identity caused by the process and practices of contact and avoidance of discussion of the damage to the parent–child relationship which, irrespective of the ultimate destination of a child in state care, cannot be obliterated.